THE RELATIONSHIP AMONG BIOLOGICAL LEARNING DIFFICULTIES WTTH AFFECTM COMPETENCE AND COGMTIyE COMPETENCE TOWARI) STUDENT OF SMUN 8 SURAKARTA IN ACADEMIC YEAR OF 2OO4/2005 - ROSYIDI, ALVI; MARYONO, MARYONO; KURNIASIH, ANISAK (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2005)
The aims of this research were to know the relationship among biologicol learning dfficulties with affective competence ond cognitive compelence and each contribution to that dfficulties toward student of SMUN 8 Surikarta. This research was carried out during academic year of 2004/2005. This was the descriptive quantitative research with ex post faclo. The threated student was sampled in amount of 40 students by simplerandom sampling. The data obtained was'then analized by multivariate-linear regression analysisThe results showed that there was significant dffirence between biological learning dfficulties with cognitive comrytence and afective comrylence. The dominant contributor to the difficulties was the affective competence (52, 29%o). This reasearch alsofound that lhere was correlation between those two competences